"Us" and "them": Corporate strategic activism, horizontal inequalities, and society's capacity to address its grand challenges. (28th February 2022) - Ganson, Brian; He, Tony L.; Henisz, Witold J.
Abstract: Research Summary: Divisions into an "us" and a "them" across racial, ethnic, economic, geographic, and other demographic divides impede society's capacity to address grand challenges. Firms have an impact on such divisions—whether positively or negatively, intentionally or not—through the dual mechanisms of rents and relationships. Firms may contribute to horizontal inequalities that underlie intergroup conflict through the distribution of the benefits, costs, and risks of firm activities. Through their relational strategies, firms also shape the willingness and ability of different groups to work together for positive change. Firm behaviors emerging from their daily operations can thus change society's capacity to address its grand challenges, necessitating corporate activism that encompasses market and nonmarket strategies, as well as a broader understanding of the strategy‐setting process itself. Managerial Summary: This paper examines how firms inevitably shape conflict and cooperation in society through their impact on relationships between groups across racial, ethnic, economic, geographic, and other demographic boundaries. Managers distribute the gains and losses of business activities in ways that differently impact identity groups attentive to their relative inequalities. Strategies regarding how stakeholder relationships are built or broken can also change the ability of groups to build consensus on issues of broad social concern. We explain how these managerial decisions can thus affect the capacity of broader society to address collective challenges. We further explore how managers can design and implement inclusive market and nonmarket strategies that strengthen the cooperative potential of different groups to advance important social goals.